Single-cell visualization of mir-9a and Senseless co-expression during Drosophila melanogaster embryonic and larval peripheral nervous system development. - Gallicchio, L.; Griffiths-Jones, S.; Ronshaugen, M. (G3 : genes - genomes - genetics, 2021)
The Drosophila melanogaster peripheral nervous system (PNS) comprises the sensory organs that allow the fly to detect environmental factors such as temperature and pressure. PNS development is a highly specified process where each sensilla originates from a single sensory organ precursor (SOP) cell. One of the major genetic orchestrators of PNS development is Senseless, which encodes a zinc finger transcription factor (Sens). Sens is both necessary and sufficient for SOP differentiation. Senseless expression and SOP number are regulated by the microRNA miR-9a. However, the reciprocal dynamics of Senseless and miR-9a are still obscure. By coupling single-molecule FISH with immunofluorescence, we are able to visualize transcription of the mir-9a locus and expression of Sens simultaneously. During embryogenesis, we show that the expression of mir-9a in SOP cells is rapidly lost as Senseless expression increases. However, this mutually exclusive expression pattern is not observed in the third instar imaginal wing disk, where some Senseless-expressing cells show active sites of mir-9a transcription. These data challenge and extend previous models of Senseless regulation and show complex co-expression dynamics between mir-9a and Senseless. The differences in this dynamic relationship between embryonic and larval PNS development suggest a possible switch in miR-9a function. Our work brings single-cell resolution to the understanding of dynamic regulation of PNS development by Senseless and miR-9a.